6-11x=14+x

Simple and best practice solution for 6-11x=14+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-11x=14+x equation:


Simplifying
6 + -11x = 14 + x

Solving
6 + -11x = 14 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + -11x + -1x = 14 + x + -1x

Combine like terms: -11x + -1x = -12x
6 + -12x = 14 + x + -1x

Combine like terms: x + -1x = 0
6 + -12x = 14 + 0
6 + -12x = 14

Add '-6' to each side of the equation.
6 + -6 + -12x = 14 + -6

Combine like terms: 6 + -6 = 0
0 + -12x = 14 + -6
-12x = 14 + -6

Combine like terms: 14 + -6 = 8
-12x = 8

Divide each side by '-12'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 3m+6=3.5m-1 | | 3(x+11)=11x-19 | | x^8-7x^7-3x^6= | | (4x+1)(2x^2+x+1)= | | 7x^3+6x^2-2= | | 2cx-1=0 | | 2c*-1=0 | | 5x+18=4x | | i=101x-201526 | | 5x-2=-27 | | 4x^2+8x+32=0 | | 32-11= | | (v+7w)x(3v+3w-1)= | | 22-42-4(x-1)-4= | | 113-7x=20x+20 | | 6x+18=328 | | 7h+4-3h+2= | | 2bc+8b-3c-12= | | x^3+8x^2+2x+16= | | 5x+12=220 | | .66a+2=1.33a+.33 | | 7a(2a-b)+3(2a-b)= | | 17z+234=2213 | | (6x^2-31x+5)(x-5)= | | 16x-18=224 | | 4a=2a+14 | | ta=ma-s | | .66a+2=1.33a+1 | | h(3)= | | (6x+7)(3x+2)= | | 21x-35=20x-45 | | 0.5n=9 |

Equations solver categories